Investigation of Polymer Flood Performance in Light Oil Reservoir: Laboratory Case Study - Dadan DSM Saputra; Bayu D Prasetiyo; Hestuti Eni; Yudha Taufantri; Ghifahri Damara; Yusuf D Rendragraha (Scientific Contributions Oil and Gas, 2022)
The use of polymer solutions in the application of chemical EOR injection technology has a role in increasing oil recovery efforts by improving oil mobility in porous media. The addition of the polymer solution is expected to increase the viscosity value of the displacement fluid so that it can form a â€œpiston-likeâ€ effect to increase the volumetric sweep efficiency of the light oil reservoir. The polymer used in this study was HPAM using 3 concentrations, namely 500 ppm, 1000 ppm, and 1500 ppm conducted at a temperature of 70 Â°C. The rheology test of the polymer included concentration vs temperature and shear rate vs viscosity. Thermal stability testing of polymer for 7, 14, 30, 60, and 90 days at 70 Â°C was done to determine the stability of the polymer solution. Filtration testing was conducted with the criteria of FR <1.2. The static adsorption test has been done with the standard limit of adsorption value <400 Âµg / gr. Polymer injectivity test using 3 variations of injection rates and coreflooding test were conducted to determine the reduction of Sor in reservoirs due to polymer displacement. From the polymer testing stage, it was found that HPAM polymers at 3 concentrations were compatible with the injection. This is indicated with the clear solution for 3 concentrations at room temperature and 70 Â°C. The rheology test results showed that the polymer solution with 3 concentrations was decreased in viscosity with the addition of the shear rate value. In the thermal stability test, the viscosity value of the HPAM with 500 ppm was relatively constant. The value of the FR for HPAM 500 ppm is 1.1, HPAM 1000 ppm is 1.07 and HPAM 1500 ppm is 1.03. The results of the static adsorption test showed the lowest HPAM value of 500 ppm was 156 Âµg/gr. In the injectivity test results, the resistance residual factor (RRF) values at injection rates of 0.3, 0.6, and 1 cc/min were 0.8, 1.04, and 1.12. The RRF value was close to 1, indicating that after injection of 500 ppm of HPAM tended to not experience plugging. Polymer flooding shows the oil recovery factor (RF) of water injection is 39% OOIP, and RF after polymer injection with 0.35 PV with flush water is 13.5% OOIP or 22% Sor. Knowing the behavior of HPAM polymer with various concentrations to be used for chemical EOR injection, it could provide advantages for future implementation in the light oil reservoir in Indonesia.